2015
DOI: 10.1002/pc.23542
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of epoxy composites with CTAB-modified BN and MWCNTs

Abstract: In this study, multi‐walled carbon nanotubes (MWCNTs) and boron nitride (BN) were functionalized with cetyltrimethylammonium bromide (CTAB) at both pH 5.5 and pH 11. These MWCNT‐CTAB and BN‐CTAB particles used to prepare the composites were dispersed in a bisphenol A (DGEBA)‐type epoxy resin (ER) system at room temperature. The TGA analysis showed that the BN composite can significantly improve the thermal stability of neat ER at temperatures above 400 °C. The curing degrees of the nanocomposites were calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…Compared to that in uncrosslinked epoxy, the band of hydroxyl groups in cured LW is more intense. The absence of epoxy ring around 913 cm −1 in all cured epoxy systems confirms the completion of the curing process, and the band at 827 cm −1 is still present in the cured epoxy spectra, which is consistent with the literature …”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Compared to that in uncrosslinked epoxy, the band of hydroxyl groups in cured LW is more intense. The absence of epoxy ring around 913 cm −1 in all cured epoxy systems confirms the completion of the curing process, and the band at 827 cm −1 is still present in the cured epoxy spectra, which is consistent with the literature …”
Section: Resultssupporting
confidence: 91%
“…Compared to that in uncrosslinked epoxy, the band of hydroxyl groups in cured LW is more intense. The absence of epoxy ring around 913 cm 21 in all cured epoxy systems confirms the completion of the curing process, and the band at 827 cm 21 is still present in the cured epoxy spectra, which is consistent with the literature [22,25] Miyagawa et al reported that the cross-linking density of ELO-toughened ER decreased with an increase in the amount of ELO added [18]. The calculated curing degrees of the M-ERs are listed in Table 1.…”
Section: Characterization Of Compositessupporting
confidence: 84%
See 1 more Smart Citation
“…Conductive polymer composites have many advantages over metallic conductors. They are lighter (in weight), provide corrosion resistance, offer a wide range of electrical conductivity and can be easily shaped with a low cost . Recently, PANI/polymer blends have attracted considerable attention since a very low amount of PANI can make the polymer conductive while maintaining the properties of the other polymer.…”
Section: Resultsmentioning
confidence: 99%
“…These values of C.D. of epoxy and epoxy composites were determined using Equation (1) used in previous studies [24][25][26]:…”
Section: Characterization Of Mwcnts and Mwcnt-epoxy Compositesmentioning
confidence: 99%